Is There a relationship Between Client Feeling Level and Categories of "Good Moments" in Counselling Sessions? - Mahrer, Alvin R.; Stalikas, Anastassios; Fairweather, David R.; Scott, Janine M. (Canadian Journal of Counselling and Psychotherapy, 2011)
This study provides a preliminary look at the relationships between strength of client feeling and categories of good moments of client movement, progress, or change. Judges rated the strength of feeling and the good moments in 105 statements of a client seen in a single session of client-centred counselling. The findings indicated significant relationships between intensity of feeling and categories of good moments. Implications are drawn for further research and for counsellor training practice.